Transparansi Pelaporan Pajak Di LPD Desa Adat Bedha Menggunakan Platform Digital Cortax - Ni Wayan Asri Pradnyani; I Gusti Agung Ayu Intan Fatmayoni; Pande Made Ari Ananta Paramarta (CV. ULIL ALBAB CORP, 2025)
LPD Desa Adat Bedha, the largest asset holder in Tabanan Regency in 2025, is recorded as the highest contributor to social funds with a contribution of IDR 2.46 billion. The annual financial report for 2024 has not been published online, so document access is only available through direct contact with LPD. This study aims to analyze the influence of using the digital platform CoreTax on the transparency of tax reporting and to identify the challenges faced by LPD in tax reporting. Data analysis employed Structural Equation Modeling Partial Least Squares SEM PLS to examine the relationships among latent variables. The results indicate that all independent variables including CoreTax system quality, user technology literacy, administrative compliance, and financial data integration have a positive and significant effect on tax report transparency. CoreTax system quality is the dominant factor. Challenges include limited technology literacy, inadequate infrastructure, inconsistent administrative compliance, limited data integration, and resistance to digitalization. The findings emphasize that system optimization, increased user capacity, and proper data integration are necessary to enhance accountability and public trust in LPD. Implementing CoreTax can improve transparency, minimize errors, and support technology-based village financial governance.